The life history of longnose emperors (Lethrinus olivaceus) and a data‐limited assessment of their stock to support fisheries management at Rangiroa Atoll, French Polynesia. Issue 3 (5th January 2022) - Filous, Alexander; Daxboeck, Charles; Beguet, Teva; Cook, Chuck
Abstract: The spawning aggregations of coral reef species support artisanal fisheries throughout the Pacific Islands, but they are vulnerable to overexploitation and need improved fisheries management. To this aim, the authors employed a combination of fishery methods including life‐history studies to estimate the age, growth and reproductive parameters of longnose emperor ( Lethrinus olivaceus ), and a length‐based stock assessment to provide the community of Rangiroa Atoll with an assessment of their longnose emperor spawning aggregation fishery. The von Bertalanffy growth parameters of this species were estimated to be L ∞  = 80 (75–87) cm TL, K  = 0.18 (0.15–0.24), t 0  = −0.82 (−1.43−0.27) with a mean natural mortality rate of 0.309 ± 0.038. The sex ratios observed in this study support the belief that this species exhibits functional protogyny with females reaching sexual maturity at 38 cm TL and approximately 3 years of age, and sex change occurring at approximately 45 cm TL and 4 years of age. The spawning potential ratio (SPR) of the longnose emperor stock was estimated to be between 19% and 28% across the years of this study, and simulations of SPR and yield per‐recruit indicate that if the community wanted to conserve >30% of the stock's SPR, the ideal minimum size limit for this species is 50 cm TL. The results provide the baseline life‐history information required to evaluate the fisheries for this species in the South Pacific region and support community‐led management actions for this spawning aggregation fishery on Rangiroa Atoll.